(untitled) (International Educators Conference, 2025)
Cytokines are traditionally the subject of special attention of researchers dealing with the problems of reproductive immunology, which is associated with their participation in the implementation of virtually all stages of the gestational process. Moreover, during pregnancy, the importance of certain factors changes due to the peculiarities of the stages of placenta formation and changes in the population composition of cytokine-producing cells in the dynamics of the gestational process. The aim of the study is to carry out a comparative analysis of cytokine production in physiologic pregnancy depending on the gestational age.